Predicting early blast transformation in chronic‐phase chronic myeloid leukemia: Is immunophenotyping the missing link?. Issue 6 (11th November 2014) - El Rassi, Fuad; Bergsagel, John D.; Arellano, Martha; Gaddh, Manila; Jillella, Anand; Kota, Vamsi; Heffner, Leonard T.; Winton, Elliott F.; Khoury, Hanna Jean
<x xml:space="preserve">Abstract</x> BACKGROUND Flow cytometry (FC) is a commonly requested test in the workup of leukocytosis in community practices. The role of FC in chronic‐phase chronic myeloid leukemia (CP‐CML) is unknown. We hypothesized that finding aberrant cells with FC in CP‐CML may predict early blast‐phase (BP) transformation. METHODS Results for FC performed at the time of diagnosis for adult and pediatric patients with CP‐CML who were referred to our institution were reviewed, and they were correlated with outcomes. RESULTS FC was performed at the time of diagnosis for 110 of 233 patients (47%) with CP‐CML. Aberrant populations, representing a median of 2% (range, 0.3%‐15%), were detected with FC in 30% of patients (33 of 110): 2 of these 33 patients expressed lymphoid markers, and 31 expressed aberrant myeloid markers. Patients received imatinib (85%), dasatinib (12%), or nilotinib (3%) as their first‐line treatment. With a median follow‐up of 43 months (range, 2‐113 months), chronic myeloid leukemia transformed to BP in 5 of the 33 patients. The 2 patients with lymphoid markers and the 3 of 31 patients with aberrant myeloid markers experienced a transformation to lymphoid BP at a median of 11 months (range, 4‐72 months) after the initiation of tyrosine kinase inhibitor therapy. Although both cases with detectable lymphoid markers rapidly progressed to lymphoid BP, the positive predictive value of BP transformation by the detection of myeloid aberrant cells with FC was only 10% (3 of 31). CONCLUSIONS In contrast to aberrant myeloid markers, the detection of lymphoid markers by FC at the time of the diagnosis of CP‐CML appears to be associated with early progression to lymphoid BP. Cancer 2015;121:872–875. © 2014 American Cancer Society.